The constitutional projects of constitutional projects of 1855: The path to the constitution of 1856 and the economic modernization - Jiyagon Villanueva, José Carlos (2018)
This article shows us the path that had to be developed to establish the Constitution of 1856, first establishing the conditions that questioned the Constitution of Huancayo, observing its marked conservatism. After the triumph of the revolution of 1854, liberal ideas triumphed which were reflected in the constitutional debate of the National Convention of 1855. The 1855 and 1856 biennium would be marked by a series of publications that sought to influence the development of the Constitution of 1856. Within all this panorama the north is the economic modernization of the Peruvian State of the XIX century.